Polystyrene microbeads modulate the energy metabolism of the marine diatom Chaetoceros neogracile - Seoane, Marta; González-Fernández, Carmen; Soudant, Philippe; Huvet, Arnaud; Esperanza, Marta; Cid, Ángeles; Paul-Pont, Ika (Environmental pollution (1987), 2019)
Due to the growing concern about the presence of microplastics (MP) in the environment, the number of studies evaluating the toxicity of these small persistent particles on different marine species has increased in recent years. Few studies have addressed their impact on marine phytoplankton, a subject of great concern since they are primary producers of the aquatic food web. The aim of this study is to unravel the cytotoxicity of 2.5 μg mL−1 unlabelled amino-modified polystyrene beads of different sizes (0.5 and 2 μm) on the marine diatom Chaetoceros neogracile. In addition to traditional growth and photosynthesis endpoints, several physiological and biochemical parameters were monitored every 24 h in C. neogracile cells by flow cytometry during their exponential growth (72 h). Dynamic Light Scattering measurements revealed the strong aggregation and the negative charge of the beads assayed in the culture medium, which seemed to minimize particle interaction with cells and potentially associated impacts. Indeed, MP were not attached to the microalgal cell wall, as evidenced by scanning electron micrographs. Cell growth, morphology, photosynthesis, reactive oxygen species levels and membrane potential remained unaltered. However, exposure to MP significantly decreased the cellular esterase activity and the neutral lipid content. Microalgal oil bodies could serve as an energy source for maintaining a healthy cellular status. Thus, MP-exposed cells modulate their energy metabolism to properly acclimate to the stress conditions. [Display omitted] •Effects of 0.5 and 2 μm PS-NH2 microplastics (MP) were evaluated on C. neogracile.•MP showed negative charge, were aggregated and were not attached to the cell wall.•Exposure to MP decreased the cellular metabolic activity and neutral lipid content.•Cells modulate their energy metabolism to properly acclimate to the stress conditions.•Microalgal oil bodies serve as an energy source for maintaining a healthy status. Diatoms' cells adjust their metabolism to cope with the stress promoted by microplastic exposure.